Surgically induced intracranial contrast enhancement: potential source of diagnostic error in intraoperative MR imaging - Knauth, Michael; Aras, Nurdagül; Wirtz, Christian Rainer; Dörfler, Arnd; Engelhorn, Tobias; Sartor, Klaus (American journal of neuroradiology, 1999)
BACKGROUND AND PURPOSE: Intraoperative MR imaging is being used increasingly during neurosurgical interventions. The aim of this study was to describe and classify different forms of surgically induced intracranial contrast enhancement observed during intraoperative MR examinations. - METHODS: A total of 51 intraoperative MR examinations were performed to assess the extent of brain tumor removal. The intraoperative MR results (T1-weighted images, unenhanced and obtained serially after the IV administration of paramagnetic contrast material) were compared with preoperative and early postoperative MR findings. Animal experiments were conducted to obtain further evidence of the mechanism of surgically induced contrast enhancement. - RESULTS: Four different types of surgically induced contrast enhancement were found: meningeal enhancement, increased enhancement of the choroid plexus, delayed enhancement at the resection margins, and immediate intraparenchymal contrast enhancement. The types of surgically induced contrast enhancement differ regarding their location, configuration, and time course. Their potential to be confused with contrast-enhancing, residual tumor also varies. Three of the four types of surgically induced contrast enhancement were reproducible in an animal model. - CONCLUSION: Surgically induced contrast enhancement is a potential source of error in intraoperative MR imaging. Careful analysis of the location, configuration, and time course of intraoperatively observed intracranial enhancement is critical to avoid confusing surgically induced contrast enhancement with contrast-enhancing, residual tumor.
Gesehen am 11.03.2021